'Gender Verification Issues in Women's Competitive Sports: An Ethical Critique of the IAAF DSD Regulation'. Issue 4 (1st October 2020) - Takemura, Mizuho
ABSTRACT: In 2018 the World Heath Organization decided to re-examine the classification of gender identity disorder and exclude it from being defined as a mental illness. This re-examination means that sex and gender do not have a single meaning It can be argued that the WHO decision presents an ethical dilemma for competitive sports, since a more concrete definition of gender is required to determine the category in which an athlete will compete without the violation of basic human rights or the violation of fair play in sport. The example of Caster Semenya illustrates the ethical dilemma that arises in this situation. In what follows, I will discuss: 1) the circumstances and background of Semenya's eligibility; 2) the conflict between moral values that arises here; 3) an ethical interpretation of the International Association of Athletics Federation (IAAF)'s claim regarding Semenya's case; and lastly 4) the acceptable level of injustice in competitive sports. From these perspectives, I will offer a practical philosophical discussion of the IAAF's new regulations using Semenya's case as an illustrative example and clarifying the difference between 'discrimination' and 'distinction'. This paper partially affirms the Differences of Sexual Development (DSD) regulations issued by the IAAF in 2018. Its intention is not to completely support the IAAF's regulations, however, but rather to show that the paradigm of modern sports itself can be a target of criticism.